An appraisal of Typilobus Stoliczka, 1871 (Crustacea, Brachyura, Leucosioidea), with description of a new family and genus - Artal, Pedro; Hyžný, Matúš (Zootaxa, 2016)
Since its description, Typilobus Stoliczka, 1871, has become something like a catch-all taxon to accommodate fossil leucosioid crabs with uncertain affinities. As many as 17 species have been assigned to Typilobus, recorded from the Eocene to Miocene strata of Europe, Africa, and Asia. The re-examination of the type species, Typilobus granulosus Stoliczka, 1871, from the Miocene of Pakistan, has shown inconsistency in its description and published figures leading to the need of a revision of all species assigned to Typilobus. Typilobus boscoi Vía Boada, 1959, from the Middle Eocene of Spain, is revised and assigned to Folguerolesia n. gen. Characters present on ventral portions of male and female specimens differ from all known representatives of Leucosioidea, although the general morphology supports inclusion in this superfamily. A new family, Folguerolesiidae n. fam. is thus erected to accommodate Folguerolesia boscoi comb. nov., leading to recognition of three families of leucosioid crabs, including Iphiculidae and Leucosiidae.